COD removal and colour degradation of textile dye effluents by locally isolated microbes. Issue 19 (30th December 2022) - Mohamad Hanapi, Nur Hanis; Sayid Abdullah, Sharifah Hanis Yasmin; Khairuddin, Zuriati; Mahmod, nor Hasima; Monajemi, Hadieh; Ismail, Azimah; Lananan, Fathurrahman; Suhaili, Zarizal; Endut, Azizah; Juahir, Hafizan
ABSTRACT: Textile industry has been rapidly progressing over the years, leading to an increasing volume of water usage that contributes to the large production of textile wastewater. Biological treatment processes have been proven to be the most environmentally friendly, cost-effective and requiring reduced production treatment by-products. In this study, using microbial treatment was applied. Three potential local isolates of micro-organism had been isolated from textile wastewater. The treatment processes were studied under two conditions, namely aerobic and anaerobic. Decolourization of seven commercial textile dyes, namely Crystal Violet 3, Acid Black 1, Basic Blue 8, Acid Blue 147, Congo R, Chrysoiodine R and Yellow 2 G were studied. After seven days of incubation, a significant reduction of 92% for Yellow 2G (Y) and 73.73%for Chrysoiodine R was observed, indicating a high capability of the bacterial isolates indye-degrading activities. Highest chemical oxygen demand (COD) removal was achieved byisolate C3K (93.93%), followed by isolate C3W (90.5%) and isolate C1 (89.173%) in nineincubation days, highlighting the ability of these microbial isolates in removing COD from the individual textile dyes.